2018
DOI: 10.32607/20758251-2018-10-1-34-42
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TNF and VEGF on the Properties of Ea.hy926 Endothelial Cells in a Model of Multi-Cellular Spheroids

Abstract: Endothelial cells play a major role in the development of inflammation and neoangiogenesis in cancer and chronic inflammatory diseases. In 3D cultures, cells are under conditions that closely resemble those existing in healthy and disease-stricken human organs and tissues. Therefore, the development of a 3D model based on the Ea.hy926 endothelial cell line is an urgent need in molecular and cellular biology. Cell cultivation on an anti-adhesive substrate under static conditions was shown to lead to the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…It has also been reported that VEGF is an important factor in HCC (35). The EA.hy926 cell line was selected for the current study based on previous studies (15)(16)(17). In line with previous findings, the present study observed that VEGF was abnormally expressed in the blood and tumor thrombus tissues of HCC patients with portal vein tumor thrombus, whereas silencing VEGF slowed down the proliferation of EA.hy926 endothelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It has also been reported that VEGF is an important factor in HCC (35). The EA.hy926 cell line was selected for the current study based on previous studies (15)(16)(17). In line with previous findings, the present study observed that VEGF was abnormally expressed in the blood and tumor thrombus tissues of HCC patients with portal vein tumor thrombus, whereas silencing VEGF slowed down the proliferation of EA.hy926 endothelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies mainly focused on the roles and signaling transductions associated with vascular endothelial growth factor (VEGF) in the progression of tumor thrombus (12)(13)(14). The excessive growth of blood vessels is one of the important conditions for the formation of tumors and tumor thrombi (15)(16)(17), therefore the EA.hy926 cell line was used in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, other culture models have been developed and used to study EC function. Among them are endothelial monolayers seeded on three‐dimensional (3D) scaffolds of collagen type I (Alekseeva, Unger, Brochhausen, Brown, & Kirkpatrick, ), ECs embedded in gels of the mentioned proteins or other materials (Murikipudi, Methe, & Edelman, ; Wang, Ali, & Lacerda, ), and 3D spheroids (Gapizov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In such manner, basolateral evaluation was able to better detect changes in cytokine secretion, highlighting the need to further investigate the role of polarised release of pro-inflammatory mediators when assessing inflammatory responses to inhaled toxicants. Increased cytokine secretion upon culture of epithelial cells in 3D has been demonstrated to better resemble in vivo situations and recruitment of immune cells after epithelial damaged is driven by secretion of cytokines and other mediators [70][71][72][73][74]. Increased detection of cytokine secretion in 3D models is believed to arise from better representation of signalling mechanisms that can remain undetected or underrepresented in 2D models [27,75,76].…”
Section: Discussionmentioning
confidence: 99%